Al-Biqai and Islahi: a comparative study of Tafsir methodology - Khan, Israr Ahmad (IIUM Press, 2003)
It is recognized by scholars that there is a system of coherence in the Qur’ān and that each and every verse, large and small, constitutes an integral unit of the Qur’ān. There are only two complete tafsīr (exegesis) of the Qur’ān based on the principle of coherence. One is in Arabic and the other is in Urdu. A comparative analysis of the two works shows that the coherence found in the Arabic exegesis was in its formative phase and that it was developed to its full form in the Urdu exegesis. The coherence in the Qur’ān found in the two exegesis deserves closer analysis as it may assist the rebuilding of the grand edifice of Islamic thought and life.